The new consumer and its evolution after COVID-19 (RAN - Revista Academia & Negocios, 2023)
Purpose: To introduce the concept of the new consumer, this study examines the concept evolution and transformation over time, exploring the behavioural changes as a result of the COVID 19 pandemic. Methodological design: A systematic literature review was conducted mainly on Scopus databases and to a lesser extent EBSCO and Google Scholar. Results: Analysis of the transformation of consumer behaviour addressing its evolution, characteristics, and main changes in its definition across the different stages of marketing, as well as the incidence of the COVID 19 pandemic in this development. This aims to introduce a forefront concept of the new consumer by compiling the up-to-date perspective of different authors. Implications: To understand the evolution, needs and preferences of consumers of the post-pandemic digital era. Originality: To identify the new consumer in times of pandemic and the organizational transformation in the face of new market needs.